Bacterial diversity and biopotentials of Hamtah glacier cryoconites, Himalaya - Singh, Purnima; Singh, Shiv Mohan; Segawa, Takahiro; Singh, Prashant Kumar (Frontiers in Microbiology, 2024)
Cryoconite is granular structures present on the glaciers and ice sheets found in Polar regions including Himalayas. It is comosed of organic and inorganic matters which absorb solar radiations and reduce ice surface albedo, therefore impact on the melting and retreat of glaciers. Though climate warming has serios impact on Himalayan glaciers, however biodiversity of sub-glacier ecosystems is poorly understood. Moreover, cryoconites holes are unique habitats for psychrophile biodiversity hotspots in the NW Himalayas, but the studies on microbial diversity of such habitat, remains elusive. Therefore, the current study was designed to explore the bacterial diversity of the Hamtah glacier Himalaya using both culturable and non-culturable approach. The culturable bacterial count ranged from 2.0 x 10 3 to 8.8 x 10 5 colony forming units (CFUs)/g at the different locations of the glacier. A total of 88 bacterial isolates were isolated using culturable approach. Based on 16S ribosomal RNA gene (16S rRNA), the identified species belong to seven genera, namely Cryobacterium, Duganella, Janthinobacterium, Pseudomonas, Peribacillus, Psychrobacter and Sphingomonas. In non-culturable approach, high-throughput sequencing of 16S rRNA genes (using MiSeq) showed unique bacterial community profiles, and represented 440 genera belonging to 20 phyla, such as Proteobacteria, Actinobacteria, Firmicutes, Bacteroidetes,